Selective induction of toxicity to human cells expressing human immunodeficiency virus type 1 Tat by a conditionally cytotoxic adenovirus vector. - Venkatesh, L K (1990)
The human immunodeficiency viruses (HIVs) primarily infect CD4+ T lymphocytes, leading eventually to the development of a systemic immune dysfunction termed acquired immunodeficiency syndrome (AIDS). An attractive strategy to combat HIV-mediated pathogenesis would be to eliminate the initial pool of infected cells and thus prevent disease progression. We have engineered a replication-defective, conditionally cytotoxic adenovirus vector, Ad-tk, whose action is dependent on the targeted expression of the herpes simplex virus type 1 thymidine kinase gene (tk), cloned downstream of the HIV-1 long terminal repeat, in human cells expressing the HIV-1 transcriptional activator Tat. Infection of Tat-expressing human HeLa or Jurkat cells with Ad-tk resulted in high-level tk expression, which was not deleterious to the viability of these cells. However, in the presence of the antiherpetic nucleoside analog ganciclovir, Ad-tk infection resulted in a massive reduction in the viability of these Tat-expressing cell lines. As adenoviruses are natural passengers of the human lymphoid system, our results suggest adenovirus vector-based strategies for the targeted expression, under the control of cis-responsive HIV regulatory elements, of cytotoxic agents in HIV-infected cells for the therapy of HIV-mediated pathogenesis.